Flores and miss paula ebook A novel. - Rivero, Melissa (2023)
A Recommended Book From: The Washington Post * Today * Sunset Magazine * Country Living * Good Housekeeping A wry, tender novel about a Peruvian immigrant mother and a millennial daughter who have one final chance to find common ground Thirtysomething Flores and her mother, Paula, still live in the same Brooklyn apartment, but that may be the only thing they have in common. It's been nearly three years since they lost beloved husband and father Martín, who had always been the bridge between them. One day, cleaning beneath his urn, Flores discovers a note written in her mother's handwriting: Perdóname si te falle. Recuerda que siempre te quise. ("Forgive me if I failed you. Remember that I always loved you.") But what would Paula need forgiveness for? Now newfound doubts and old memories come flooding in, complicating each woman's efforts to carve out a good life for herself—and to support the other in the same. Paula thinks Flores should spend her evenings meeting a future husband, not crunching numbers for a floundering aquarium startup. Flores wishes Paula would ask for a raise at her DollaBills retail job, or at least find a best friend who isn't a married man. When Flores and Paula learn they will be forced to move, they must finally confront their complicated past—and decide whether they share the same dreams for the future. Spirited and warm-hearted, Melissa Rivero's new novel showcases the complexities of the mother-daughter bond with fresh insight and empathy.